The Economics of Prostitution: How Does Prostitution Affect Family Resilience? - Budiantoro, Risanda; Rachman, M. Aulia; Aji, Mario R.W.; Putra, Febrianur I.F.S.; Perdana, Tito A. (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2025)
Objective: This study aims to formulate an ideal government policy that addresses prostitution comprehensively. Method: This study applies a qualitative descriptive-normative method. The data were obtained through secondary sources, document analysis, participatory and direct observations, as well as semi-structured interviews. Data analysis was conducted using an inductive approach through data reduction, classification, and interpretation. Triangulation methods were employed to ensure the validity and credibility of the data. Result: The study reveals that the prostitution business in Indonesia is supported by complex networks involving pimps, sex workers, clients, and other indirect actors. The practice is driven by multiple factors including economic necessity, social vulnerability, low moral awareness, and inadequate family resilience. Additionally, prostitution has created both positive and negative externalities in the surrounding communities, especially in urban areas. Implication: This study suggests that government policies must be integrative, addressing not only the legal aspects but also offering economic empowerment programs, family resilience development, and moral education. The findings highlight the importance of collaboration between state institutions, religious leaders, and community organizations to reduce the dependence on prostitution as a means of livelihood. Novelty: This research offers a comprehensive framework by linking the economic, religious, and sociological dimensions of prostitution. Unlike prior studies that focus on a single aspect, this study presents prostitution as a systemic issue within the informal economy that requires a multi-sectoral and ethically grounded policy response